2021
DOI: 10.1155/2021/9811361
|View full text |Cite
|
Sign up to set email alerts
|

Ocular TGF-β, Matrix Metalloproteinases, and TIMP-1 Increase with the Development and Progression of Diabetic Retinopathy in Type 2 Diabetes Mellitus

Abstract: Diabetic retinopathy (DR) is a sight-threatening late complication of diabetes mellitus (DM). Even though its pathophysiology has not been fully elucidated, several studies suggested a role for transforming growth factor- (TGF-) β, matrix metalloproteinases (MMPs), and tissue inhibitors of matrix metalloproteinase (TIMP) in the onset and progression of the disease. Consequently, the aim of this study was to analyze the concentrations of TGF-β1, TGF-β2, TGF-β3, MMP-3, MMP-9, and TIMP-1 in patients with differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…TIMP-1 is a strong inhibitor of most matrix metalloproteinases (MMP), and the balance between them may be critical to tissue homeostasis in DR ( 69 ). Studies have reported elevated levels of TIMP-1 in vitreous fluid in the PDR, and some studies have shown that the balance between TIMP-1 and MMP may be disrupted early in the onset of DR ( 69 71 ). In late NPDR/PDR, the concentration of TIMP-1 in aqueous humor increased, but there was no significant change in serum, indicating that its intraocular regulation was independent of systemic regulation, and that TIMP-1 was involved in the progression of DR ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIMP-1 is a strong inhibitor of most matrix metalloproteinases (MMP), and the balance between them may be critical to tissue homeostasis in DR ( 69 ). Studies have reported elevated levels of TIMP-1 in vitreous fluid in the PDR, and some studies have shown that the balance between TIMP-1 and MMP may be disrupted early in the onset of DR ( 69 71 ). In late NPDR/PDR, the concentration of TIMP-1 in aqueous humor increased, but there was no significant change in serum, indicating that its intraocular regulation was independent of systemic regulation, and that TIMP-1 was involved in the progression of DR ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported elevated levels of TIMP-1 in vitreous fluid in the PDR, and some studies have shown that the balance between TIMP-1 and MMP may be disrupted early in the onset of DR ( 69 71 ). In late NPDR/PDR, the concentration of TIMP-1 in aqueous humor increased, but there was no significant change in serum, indicating that its intraocular regulation was independent of systemic regulation, and that TIMP-1 was involved in the progression of DR ( 71 ). BMP-7, a member of BMPs, interacts with TGF- β and participates in the process of tissue degeneration and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is increasing evidence that transforming growth factor beta (TGF-β) signaling plays a critical role in DR. In fact, TGF-β1 expression in DR patients, DR rats, and high glucose-incubated human retinal endothelial cells (HRECs) and human adult retinal pigment epithelial cells (ARPE-19) is increased [ 4 , 5 , 6 , 7 ], possibly representing a target of anti-fibrotic therapy during DR.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have used the high glucose (HG)-induced human retinal pigment epithelial (RPE) cell line ARPE-19 to investigate the DR pathogenesis [ 10 ]. In HG-induced ARPE-19 cells, several pathological changes are associated with DR, including the upregulation of vascular endothelial growth factor (VEGF) [ 11 ]; transforming growth factor (TGF) [ 12 , 13 ]; matrix metalloproteinases [ 14 , 15 , 16 ]; inflammatory cytokines [ 17 ]; oxidative stress [ 18 , 19 , 20 , 21 ]; and genetic factors [ 22 , 23 , 24 ]. However, few studies have investigated the relationship between autotaxin (ATX) and DR.…”
Section: Introductionmentioning
confidence: 99%